Sociological Elements in Economic Thought - Parsons, Talcott (Quarterly Journal of Economics, 1935)
I. "Orthodox" economic theory, 415. — II. Classification of "unorthodoxies, " 420. — III. Positivistic empiricism (1) Supplementary type, 424. — IV. Positivistic empiricism (2) Radical rejection, 435. — V. "Romantic" empiricism (1) Supplementary type, (2) Radical rejection, 442. — Conclusion, 451.